Adam of Dryburgh, Soliloquium de instructione animæ - Damian-Grint, Peter (The Innes review, 2023)
Adam of Dryburgh (d.1212) was one of the greatest theologians of the Premonstratensian Order in the twelfth century. His most popular work was his Soliloquium de instructione anime, a handbook on religious life in the form of a dialogue between Anima, a dissatisfied novice, and a fatherly novice-master Ratio. Lively, realistic and entertaining, their conversation covers all kinds of difficulties a novice might face, from having to keep silence or abstain from meat, to temptations against chastity, the ordeal of being accused of faults against the Rule or having to confess to one's own abbot, leading Anima through arguments and exhortations to a more profound and supernatural understanding of his vocation. This edition and translation, based on fifteen manuscripts (some not previously known), presents the newly identified earliest redaction of Adam's text, which contains a significant amount of material missing from later versions. Also included are details of all known manuscripts of the text.